Laser ablation synthesis of silver nanoparticle in graphene oxide and thermal effusivity of nanocomposite - Sadrolhosseini, Amir Reza; Muhammad Noor, Ahmad Shukri; Mahdi, Mohd Adzir; Kharazmi, Alireza; Zakaria, Azmi; Mat Yunus, Wan Mahmood; Huang, Nay Ming (IEEE, 2013)
In this study, the silver nanoparticle was prepared in graphene oxide by using laser ablation technique. The silver plate immersed in graphene oxide, and irradiated by Q-switch Nd:YAG laser at 532 nm wavelength during 10, 15, 30 and 60 minutes. The size and concentration of silver nanoparticle (Ag-NPs) shifted from 38 nm to 8 nm and 1.3 ppm to 9.6 ppm, respectively. Thermal effusivity was measured by using photoacoustic technique, and the results were analyzed using Rosencwaig-Gersho theory. This results shows the thermal effusivity of nanocomposite was increased with an increasing the concentration of silver nanoparticle from 0.1875 to 0.1979 W.s1/2.cm-2 .K-1.